Parents' Perceptions of The Implementation of School Children's Health Protocols During the Covid 19 Pandemic - Ika Tristanti; Noor Cholifah (Urecol Journal. Part C: Health Sciences, 2021)
Indonesia had become the country with the highest death rate due to COVID 19 in the world. The incidence of COVID 19 in children was approximately 13 percent and 1.1 percent of them died. Efforts to prevent the transmission of COVID 19 have been carried out, one of which was by implementing a clean and healthy lifestyle including for children. Parents and teachers in schools should be able to ensure the safety of children when moving at home and at school. The purpose of this study was to illustrate parents' perceptions about the implementation of school children's health protocols during the COVID 19 Pandemic. This research method was quantitative with descriptive research design. The implementation of research on July 1-30, 2021 in Kudus Regency. The sample number of 216 people with sampling techniques was accidental sampling. Data analysis uses univariate analysis of parents' perceptions of the implementation of school children's health protocols during the COVID 19 pandemic. Results of research: As many as 86% of parents agree to carry out learning activities outside the home (school). 31% of parents agree with online learning. 81% of parents agree on a face-to-face learning plan for their child. 92% of parents agreed to implement health protocols during school. 66% of parents agree that children are able to discipline the health protocols in school. A total of 73% of parents agreed that teachers conduct supervision for the prevention of COVID 19.A total of 64% of parents agreed to the safety of children entering school during the COVID 19 Pandemic.